Increasing the Efficiency Factor of Solar Power Plants Due to Solar Energy Localizing - V. I. Mironchuk; A. A. Velchenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2021)
The article presents an analysis of the state of development of solar energy in Europe and  the  Republic  of  Belarus  for 2020.  An algorithm for increasing the efficiency factor of  solar power plants by localizing the solar trajectory depending on the latitude and longitude of the area has been proposed. In particular, taking into account the angle of the Sun position above the horizon and the azimuth angle of the Sun, the increase in the efficiency factor of solar power plants for the Republic of Belarus is calculated. Based on this algorithm, a program has been written that makes it possible to draw a diagram of the solar trajectory. An analysis has been made of the degree of localization of solar energy for solstice days in 6 oblast (regional) centers of the Republic of Belarus; it is found that the highest intensity of solar radiation is observed in Brest and Gomel, the average in Grodno, Minsk and Mogilev, while the lowest one – in the city of Vitebsk. A comparative analysis of the solar trajectory of the city of Berlin (Germany) with the city of Gomel and the city of Brest is carried out. Recommendations have been developed for the effective operation of solar power plants in the oblast (regional) cities of the Republic of Belarus during the year in an autonomous and combined mode of operation. The obtained numerical calculations of the solar trajectory make it possible to optimize the orientation of solar panels for permanently installed panels and for automated solar tracking systems, as well as to select the optimal configuration of the power plant equipment for any geographic area.